2016
DOI: 10.1165/rcmb.2015-0071oc
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Regulate Tight Junction Permeability of Lung Epithelia by Modulating Claudin 8

Abstract: The lung epithelium constitutes a selective barrier that separates the airways from the aqueous interstitial compartment. Regulated barrier function controls water and ion transport across the epithelium and is essential for maintaining lung function. Tight junctions (TJs) seal the epithelial barrier and determine the paracellular transport. The properties of TJs depend especially on their claudin composition. Steroids are potent drugs used to treat a variety of airway diseases. Therefore, we addressed whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…1b). Immunohistological experiments revealed that the epithelia of cartilaginous and non-cartilaginous airways is positive for cldn1, cldn2, cldn3, cldn4, cldn5, cldn7 and cldn8 [24, 62, 63, 66]. However, the intracellular localisation of these claudins differs.…”
Section: Tight Junctions Of Airway Epitheliamentioning
confidence: 99%
See 3 more Smart Citations
“…1b). Immunohistological experiments revealed that the epithelia of cartilaginous and non-cartilaginous airways is positive for cldn1, cldn2, cldn3, cldn4, cldn5, cldn7 and cldn8 [24, 62, 63, 66]. However, the intracellular localisation of these claudins differs.…”
Section: Tight Junctions Of Airway Epitheliamentioning
confidence: 99%
“…Cldn2 is localised in intracellular stores rather than in apico-lateral TJ complexes [62]. In contrast, cldn3, cldn5 and cldn8 were detected exclusively in TJ complexes [24, 66], and cldn1 and cldn4 localise throughout the lateral membranes as well as to the apico-lateral TJ complexes [24]. Cldn7 localises at the lateral membranes basolateral of the TJ complex [24].…”
Section: Tight Junctions Of Airway Epitheliamentioning
confidence: 99%
See 2 more Smart Citations
“…Claudins are tetraspanin transmembrane proteins that interact with structural proteins to form the barrier that impacts the selective permeability observed between epithelial cells [20,21]. Cldn-3 and Cldn-18 [11,22] are family members abundantly expressed in the lung; however, additional Cldn proteins have been implicated in lung development and in the maintenance of normal lung physiology [20,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%